Sistem Pendukung Keputusan Evaluasi Kinerja Dosen Program Studi Rekayasa Keamanan Siber Berbasis Website Menggunakan Metode Fuzzy Tahani - Noor, Faiz Nesa Aulia; Perdana, Danis Putra; Wulan, Puspa Ira Dewi Candra; Syarif, Khamarudin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research applies the Fuzzy Tahani method to a decision support system for evaluating the performance of faculty members in the Cyber Security Engineering Study Program at Bhakti Semesta Polytechnic. The Fuzzy Tahani method is expected to assist in processing data from faculty performance evaluation questionnaires and improve the accuracy of reporting and calculations. The Research and Development method is used as an approach to systematically address the issues. The decision support system for faculty performance assessment was successfully developed using the Fuzzy Tahani method with PHP programming language. This system is expected to help determine the level of student satisfaction with faculty performance and enhance faculty effectiveness. The test results show that the employed Fuzzy Tahani method achieved 100% accuracy, comparing manual calculations with the system's calculations. With the implementation of this system, the processing of faculty performance evaluation data becomes more efficient and accurate.